The theory and practice of group psychotherapy - Yalom, Irvin D., 1931-; Leszcz, Molyn, 1952- (New York Basics books, 2020)
"In this completely revised and updated sixth edition, Dr. Yalom and his collaborator Dr. Molyn Leszcz draw on a decade of new research as well as their broad clinical wisdom and expertise. Each chapter is completely updated in accordance with the most recent developments in the field. There are new sections throughout, including discussions of mindfulness, CBT, modern analytic approaches, psychoeducational groups, group therapy for veterans, and group therapy for psychological trauma"--
Includes bibliographical references and index.
Keywords: Group psychotherapy